Acute Intestinal Obstruction due to Complicated Meckel’s Diverticulum in an Adult: A Case Report - Arundhati Negi; Geofia Shaina Crasta; Bharath Kumar Bhat (International Journal of Anatomy Radiology and Surgery)
Meckel’s Diverticulum (MD) occurs in about 2% of the population. Symptomatic MD after the age of 50 years is extremely rare. Hereby, the authors present a case of MD in a 54-year-old female with no previous surgeries, who presented with features suggestive of intestinal obstruction. Diagnostic laparoscopy revealed that the cause of the obstruction was an inflamed MD with a band extending to the inferior aspect of the liver. A laparoscopic release of the band was performed, along with resection of the diverticular segment and the inflamed segment of the ileum, followed by end-to-end anastomosis. The patient recovered well with no postoperative complications. MD causing intestinal obstruction in a middle-aged population is extremely rare and requires careful attention for diagnosis; it is almost always discovered through surgery.